The Role of Bakumpai Dayak Women in Islamic Religious Education in the Barito River Basin Area - Wahidah Wahidah; Zulfa Jamalie (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Islamic Religious Education (PAI) plays an important role in shaping the character and moral values of Muslim communities. In the Barito River Basin area, PAI has a strategic role in improving the quality of life of the Dayak Bakumpai community, which is predominantly Muslim. However, the development of Islamic religious education in this region still faces several challenges, such as the limited availability of qualified human resources, inadequate educational facilities, and the low level of community awareness regarding the importance of religious education. In this context, Dayak Bakumpai women have a significant role in strengthening religious education within both family and community environments. They not only function as housewives but also act as educators, motivators, and social actors who support religious learning activities. Nevertheless, their contribution to the development of Islamic religious education has not been fully optimized and often receives limited attention. Therefore, this study aims to examine the role of Dayak Bakumpai women in improving the quality of Islamic Religious Education in the Barito River Basin, as well as to identify factors that influence their participation and strategies to strengthen their role in the community. This research uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The findings show that Dayak Bakumpai women play an important role in strengthening religious values, providing informal religious education in families, and supporting community religious activities. However, their role is still constrained by limited educational facilities, access to resources, and social support. Strengthening community awareness and empowering women can help optimize their role in improving the quality of Islamic religious education in the region